2004
DOI: 10.1098/rstb.2004.1471
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms regulating regeneration of deer antlers

Abstract: Deer antlers are the only mammalian appendages capable of repeated rounds of regeneration; every year they are shed and regrow from a blastema into large branched structures of cartilage and bone that are used for fighting and display. Longitudinal growth is by a process of modified endochondral ossification and in some species this can exceed 2 cm per day, representing the fastest rate of organ growth in the animal kingdom. However, despite their value as a unique model of mammalian regeneration the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 123 publications
(129 reference statements)
2
79
0
1
Order By: Relevance
“…Many studies have shown that genes implicated in early embryonic development are reactivated during blastema formation in zebrafish [106][107][108][109][110] and amphibians [111,112]. In a mammalian context, there is a marked overlap between the molecular mechanisms that control maintenance of the antler progenitor cells and developmental pathways in regenerating deer antlers [113,114]. Deer antlers are the only mammalian organ capable of complete epimorphic regeneration and so may become an important model for mammalian tissue regeneration [115,116].…”
Section: Nuclear Reprogrammingmentioning
confidence: 99%
“…Many studies have shown that genes implicated in early embryonic development are reactivated during blastema formation in zebrafish [106][107][108][109][110] and amphibians [111,112]. In a mammalian context, there is a marked overlap between the molecular mechanisms that control maintenance of the antler progenitor cells and developmental pathways in regenerating deer antlers [113,114]. Deer antlers are the only mammalian organ capable of complete epimorphic regeneration and so may become an important model for mammalian tissue regeneration [115,116].…”
Section: Nuclear Reprogrammingmentioning
confidence: 99%
“…Antler nerves grow through the velvet in close association to blood vessels in an environment rich in growth promoting molecules [20]. The AV is shed in coincidence with a great increase in testosterone concentration occurring before the rut onset [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Gonyea & Ashworth, 1975;Blackburn, Hanken & Jenkins Jr, 2008) and horns or antlers (e.g. CluttonBrock, 1982;Price & Allen, 2004). The use of ribs as 'concealed' weapons, however, is known only from two phylogenetically closely related salamander genera: Pleurodeles and Echinotriton (Leydig, 1879;Nowak & Brodie Jr, 1978;Brodie Jr, 1983;Brodie Jr et al, 1984).…”
Section: Discussionmentioning
confidence: 99%